2021
DOI: 10.1002/lary.29920
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Postoperative Nausea and Vomiting After Endoscopic Skull Base Surgery

Abstract: Objectives/Hypothesis: The objective of this study is to evaluate the impact of patient and surgical factors, including approach and reconstruction type, on postoperative nausea and vomiting episodes following endoscopic skull base surgery.Study Design: Retrospective review.Methods: We performed a retrospective chart review from July 2018 to August 2020 of 99 consecutive patients undergoing endoscopic skull base surgery at a tertiary academic skull base surgery program. All patients were treated with a standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In a retrospective study of 99 ESBS patients receiving a standardized perioperative antiemetic regimen, Birkenbeuel et al. demonstrated that an extended surgical approach was associated with higher incidence of PONV 25 . Similarly, cavernous sinus tumor involvement was associated with an increased likelihood of postoperative vomiting only.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a retrospective study of 99 ESBS patients receiving a standardized perioperative antiemetic regimen, Birkenbeuel et al. demonstrated that an extended surgical approach was associated with higher incidence of PONV 25 . Similarly, cavernous sinus tumor involvement was associated with an increased likelihood of postoperative vomiting only.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, providers should consider modifiable risk factors for PONV after ESBS, including, but not limited to, female sex, cavernous sinus dissection, and extended surgical approach, when designing an antiemetic protocol. 25 Similar to prophylactic antiemetics, there is little evidence on the role of prophylactic anticoagulation and restarting preoperative antiplatelet/anticoagulation agents after ESBS. However, with a low event rate overall and apparent minimal risk involved with both mechanical and chemical prophylaxis, consideration should be given to routine anticoagulation following ESBS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We would like to thank Onal and Onal for their letter to our manuscript entitled "Predictors of Postoperative Nausea and Vomiting After Endoscopic Skull Base Surgery" 1 and for the opportunity to respond to their comments. One of the concerns raised was that our analysis did not account for possible postoperative nausea and vomiting (PONV) events in the postanesthesia care unit (PACU), which Onal and Onal postulated may have extended patients' PACU stays and potentially leading to a nonsignificant finding in the study.…”
mentioning
confidence: 99%